2016
DOI: 10.1111/dth.12415
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hair shedding among women

Abstract: Hair shedding in female patients is a frequent complaint in dermatological, endocrinological, and gynecological consults. Previously, the Sinclair Hair Shedding Scale was developed to assess normal versus excessive hair shedding in female pattern hair loss (FPHL) subjects. However, the prevalence of hair shedding in females not suffering from FPHL is unknown. To gain better understanding of hair shedding in the general population, we recruited 300 subjects visiting a public hospital for conditions other than a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
(6 reference statements)
0
11
1
1
Order By: Relevance
“…male pattern alopecia reaching a prevalence of 50% by the age of 50 years) and increased hair shedding in female patients may be related to various aetiologies, including dermatological, endocrinological, nutritional disorders, stress, inflammatory and infectious disorders, or drug administration. [23][24][25] Although hair abnormalities have previously been attributed to PC, especially PC-2 associated with KRT17 mutations, based on the results of the current study and other previous reports, 26 it is impossible to draw any conclusions regarding a direct association between PC and hair anomalies. Corneal findings and hearing loss were previously attributed to PC in isolated reports; 11,14,22,27 however, ocular anomalies were rare in patients with PC (4%).…”
Section: Other Clinical Featurescontrasting
confidence: 76%
“…male pattern alopecia reaching a prevalence of 50% by the age of 50 years) and increased hair shedding in female patients may be related to various aetiologies, including dermatological, endocrinological, nutritional disorders, stress, inflammatory and infectious disorders, or drug administration. [23][24][25] Although hair abnormalities have previously been attributed to PC, especially PC-2 associated with KRT17 mutations, based on the results of the current study and other previous reports, 26 it is impossible to draw any conclusions regarding a direct association between PC and hair anomalies. Corneal findings and hearing loss were previously attributed to PC in isolated reports; 11,14,22,27 however, ocular anomalies were rare in patients with PC (4%).…”
Section: Other Clinical Featurescontrasting
confidence: 76%
“…A significant amount of women report excessive shedding after washing their hair . To date, no treatment is available for the reduction of hair shedding caused by the mechanical stress of everyday washing and styling.…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of women report excessive shedding after washing their hair. 3 To date, no treatment is available for the reduction of hair shedding caused by the mechanical stress of everyday washing and styling. Previously, our group demonstrated that a solution containing synephrine hydrochloride significantly reduced hair shedding during brushing.…”
Section: Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To aid physicians in their assessment of shedding, a visual‐analog scale was developed, the Sinclair Hair Shedding Scale (Sinclair, ). In a survey of 300 subjects visiting a public hospital for conditions other than alopecia, approximately 40% reported experiencing excessive hair shedding as defined by the Sinclair Hair Shedding Scale (Kovacevic et al, ).…”
Section: Introductionmentioning
confidence: 99%